The Inertia of Mass and the Newtonian Force - Kneubil,Fabiana Botelho (2021)
In this paper a relation between inertia of mass and force is presented. In educational contexts, the inertia is generally associated with momentum and energy. However, a direct connection between inertia and force can be also verified in a simple instance of collision. The description of this situation, from the action-reaction pair forces perspective, enlarges the meaning of inertia and highlights the coherence of Newtonian mechanics and the interrelation between concepts and their three laws.